Election Night at Bruce Bronzan State Assembly Campaign Headquarters in Roos-Atkins Building - Watkins, Howard::::::::: (1978)
Bruce Bronzan on stage speaking to supporters; Mark Wall, Robert Quesada,?, David Brodie, Janice Westerling, Linda Bronzan, Bill Carlson, Randy Walsh, Doug Jones, Marsha Smith Watkins, ??, Sandy Walsh, Tony Correia, ??